2020
DOI: 10.1155/2020/4790254
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Migraine Headache in Arab Countries: A Systematic Review

Abstract: Background. Recurring migraine disorders are a common medical problem, standing among the top causes of disability and sufferings. This study aimed to evaluate epidemiological evidence to report updated estimates on prevalence, risk factors, and associated comorbidities of migraine headache in the Arab countries. Design and Setting. A systematic review was conducted at the College of Public Health and Health Informatics, Riyadh, Saudi Arabia. Methods. A systematic search in electronic databases, such as PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 57 publications
(62 reference statements)
4
38
2
2
Order By: Relevance
“…In parallel, common genetic polymorphisms at CALCB have been reported to contribute to diverticular disease that is a common of intestinal neuromuscular function 70 . Of note, several epidemiologic studies reported that gastrointestinal disorders such as the “irritable bowel syndrome” are the most commonly reported comorbidities associated with migraine 71 , 72 . Our results suggest that the relationship between the intestine and migraine, also referred to “gut-brain axis,“ could have some genetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, common genetic polymorphisms at CALCB have been reported to contribute to diverticular disease that is a common of intestinal neuromuscular function 70 . Of note, several epidemiologic studies reported that gastrointestinal disorders such as the “irritable bowel syndrome” are the most commonly reported comorbidities associated with migraine 71 , 72 . Our results suggest that the relationship between the intestine and migraine, also referred to “gut-brain axis,“ could have some genetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, females had a higher prevalence of migraine and IBS than males. This observation has been thoroughly established in the literature pertaining to Arab nations as well as globally [2,13,29,30]. Females showed not only a higher prevalence of migraine and IBS, but also the bivariate and regression analysis demonstrated that females had a higher probability of having migraine and IBS.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, females had a higher prevalence of migraine and IBS than males. This observation has been thoroughly established in the literature about Arab nations and globally [ 2 , 13 , 34 , 35 ]. Females showed a higher prevalence of migraine and IBS, and the bivariate and regression analysis demonstrated that females had a higher probability of having migraine and IBS.…”
Section: Discussionmentioning
confidence: 77%